Hydrodynamics of a Bordered Collar as a Countermeasure against Pier Scouring - Domenico Ferraro; Andrea Fenocchi; Roberto Gaudio (Environmental Sciences Proceedings, 2022)
Countermeasures against local scour at bridge piers and abutments can be grouped into two categories: (1) flow-altering and (2) bed-armouring countermeasures. In this work, long-term laboratory-scale experiments of clear-water scour at bridge piers with different configurations were performed in order to investigate the effects of an unprotected cylindrical pier, of a cylindrical pier with a classic collar countermeasure and of a cylindrical pier with a modified collar countermeasure. Tests were performed in a flume with movable sediment bed, and the scoured bathymetries at the equilibrium stage were acquired and used in numerical simulations of small-scale hydrodynamics at the piers. The modified collar countermeasure resulted in a significant reduction of the scour hole dimensions.